Modalities and Identity Politics of The Marbun Clan In Humbang Hasundutan Regency - Kevin Nathanael Marbun; Jonah Silas (Epistemik Press, 2022)
In the Humbang Hasundutan Regency Local Leaders Election, the identity of the Marbun clan was used as a tool of political struggle to win candidates. The considerations underlying this research are the experience of the Marbun clan who lost in the previous two elections and the impact felt by the defeat, specifically: an uneven development focus and officials from the Marbun clan who rarely occupy positions in the government. Identity politics can be understood as a tool of political struggle of an ethnicity in an effort to achieve a goal. Identity politics is used as a tool based on two aspects, there are: based on similarity of identity and based on similarity of interests. The author uses qualitative methods with case studies. Data collection is obtained from the results of collecting primary data and also secondary data. Primary Data is obtained from the results of recorded and collected interviews. All the data obtained are analyzed qualitatively so that what is contained behind a reality can be revealed. The result of this study is that the clan plays a role in a person's political life so that the identity politics of the Marbun clan is used as a tool of political struggle from candidates in the main way to gain support through an approach to the Marbun clan group, called PTMI (Parsadaan Toga Marbun Indonesia) Humbang Hasundutan Regency and Mabun clan figures because of the community's obedience to these figures and the nature of loving and helping each other among the siblings of the three clans on Toga Marbun, they are: Lumban Batu, Banjarnahor, and Lumban Gaol.